2021
DOI: 10.3390/ani11041137
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Scrapie Prion Infection in Ovine Bone Marrow-Derived Mesenchymal Stem Cells and Ovine Mesenchymal Stem Cell-Derived Neurons

Abstract: Scrapie is a prion disease affecting sheep and goats and it is considered a prototype of transmissible spongiform encephalopathies (TSEs). Mesenchymal stem cells (MSCs) have been proposed as candidates for developing in vitro models of prion diseases. Murine MSCs are able to propagate prions after previous mouse-adaptation of prion strains and, although ovine MSCs express the cellular prion protein (PrPC), their susceptibility to prion infection has never been investigated. Here, we analyze the potential of ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…The presence/absence of PrP Sc in the CNS tissues was confirmed with two rapid diagnostic tests (Prionics-CheckWestern blotting; ThermoFisher Scientific and Idexx HerdChek; IDEXX, Westbrook, ME, USA) as previously descried [ 43 ]. CNS homogenates and microbe safety tests were prepared as described in previous works [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The presence/absence of PrP Sc in the CNS tissues was confirmed with two rapid diagnostic tests (Prionics-CheckWestern blotting; ThermoFisher Scientific and Idexx HerdChek; IDEXX, Westbrook, ME, USA) as previously descried [ 43 ]. CNS homogenates and microbe safety tests were prepared as described in previous works [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…To test the ability to replicate PrP Sc of 2D oBM-MSCs and spheroids inoculated with scrapie-infected brain homogenate in growth and neurogenic conditions, the amount of pathogenic protein was quantified by ELISA at 2, 5, and 8 dpi using the EEB-Scrapie HerdCheck kit (IDEXX) and following the manufacturer’s recommendations. A previous study conducted by our group showed that this kit was suitable for the sensitive detection of PrP Sc in oBM-MSC cultures [ 35 ]. oBM-MSCs were seeded at 5000 cells/cm 2 in 6-well plates, and the retrieval of the cells was performed by means of trypsinization and subsequent centrifugation to obtain 3 technical replicates per condition and time (dpi).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The meta-analysis reported by the Authors showed that stem-cell therapy may improve heart function in large animal models and that the swine species is confirmed as a relevant animal model in the cardiovascular field. In this context, there is also the study of Garcia-Mendivil et al [ 3 ] regarding the development of in vitro cellular models using ovine MSCs for prion neurodegenerative disorders affecting both humans and animals, particularly ruminants. Indeed, the response of ovine bone marrow-derived MSCs and their neuron-like derivatives to prion infection allowed us to find that BM-MSC-derived neuron-like cells could be a good candidate for developing in vitro studies.…”
mentioning
confidence: 99%